Buildig knowledge and knowers in writing retreats: Towards developing the field of higher education teaching and learning - Winberg, C.; Jacobs, C.; Wolff, K. (South African Journal of Higher Education, 2017)
Writing for publication is essential for disseminating research findings, sharing initiatives and innovations with others, and developing the knowledge base of intellectual fields. This study explores the role of writing retreats in building knowledge and knowers in the field of Higher Education Studies, specifically within the area of higher education pedagogy. We conceptually frame our research with Legitimation Code Theory (Maton 2014) in order to analyse the different ways in which participants in writing retreats orientate themselves to the social practice of writing for publication and the knowledge base of higher education pedagogy. The data comprise participants’ feedback on writing retreats, collected from surveys and focus group interviews at two universities (a teaching-intensive university and a research-intensive university), and supplementary institutional data on retreat participants and their writing achievements. By examining the organising principles of the writing retreats in terms of how they build knowledge and knowers, we make explicit the knowledge-building practices that underpin successful writing retreats and the orientations towards these practices that are productive for potential authors.